Transgender Survival Strategy Amidst Discrimination to Meet Economic Needs in Jayapura City - Amila, Amila; Abidin, Muhammad Zainal (Institut Agama Islam Negeri Ponorogo, 2024)
This research aims to uncover the experiences and strategies of transgender individuals (waria) in facing economic challenges and social discrimination. The method employed is descriptive qualitative, utilizing data collection techniques including observation, interviews, and documentation. Analysis involves data reduction, presentation, and drawing conclusions.The findings reveal that waria often face discrimination in exercising their rights as citizens, encountering difficulties in obtaining employment, education, and healthcare. They frequently experience mockery and ridicule from their surroundings, even becoming subjects of online harassment. This arises due to a lack of societal awareness regarding the existence of waria, which is perceived as different from societal norms. Despite these challenges, waria employ various strategies to meet their economic needs. They engage not only in sex work or beauty industry management but, under necessity, seek assistance from their community that understands their circumstances. Notably, previous studies have yet to address the strategies employed by waria in meeting their needs amidst the discrimination they face.